Learning Media Using Qr Code-Based Professional Pdf Flips as an Effort to Improve Students' Concept Understanding in PAI Lessons - Suci Prihatiningtyas; Filla Hidayatul Mar'ah; Dian Kusuma Wardani; Asiyah Lu’lu’ul Husna (SCHOOLAR: Social and Literature Study in Education, 2022)
The learning process that is expected in the digital era is the existence of learning interactions that take place in an interesting, up-to-date, efficient, practical and not boring manner. The purpose of this study was to determine the influence and increase in students' understanding of concepts through the implementation of E-Module learning media with QR Code-based Flip PDF Professional in PAI lessons at SMAN Plandaan Jombang. This study used the One Group Pretest-Posttest Design. The population in this study were students of class XI IPS SMAN Plandaan Jombang. The sample in this study was taken from class XI IPS 3 at SMAN Plandaan Jombang. The data collection technique in this study was by giving pre-test and post-test. The research instrument was a multiple choice test with 30 items and 5 description questions. Data analysis was performed using the prerequisite test and the N-gain test. Based on the results of the study, it was shown that the average N-Gain value in this study was 0.51 in the moderate category. The conclusions in this study indicate that the application of E-Module learning media with Flip PDF Professional can improve students' understanding of the concepts of class XI IPS 3 at SMAN Plandaan Jombang.